Analisis Protokol Routing Directed Diffusion dan Gossiping pada Wireless Sensor Network - Irvan Wahyu Bagus Pratama; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
A group of several node that have the ability to gather data, process, store data, and communicate between the node referred to by a Wireless Sensor Network (WSN). To meet the needs of the wsn in communicating at all conditions required the routing protocol must suspense the conditions needed. Some examples of the routing algorithm that already there are gossiping and directed diffusion. This research is done to compare the performance of routing protocol directed diffusion protocol with routing gossiping. Each routing protocol will be tested using network simulator-2. The results of this research will show the value of the end-to-end delay, packet delivery ratio and routing overhead of the routing protocol directed diffusion as well as routing protocol gossiping. From the test results, the results show that directed diffusion is better in a number of parameters such as a higher level of PDR in static and mobile conditions and also the average end-to-end delay value in static conditions, while gossiping is superior to the average end-to-parameter end delay on mobile conditions and routing overhead level on static and mobile conditions. It can be concluded that each routing protocol, both directed diffusion and gossiping, has the advantage of each parameter depending on the condition of the area needed in the field.